Impact, Stimulus and Life After The Economi Crisi During The Covid-19 Pandemic: Case Studies In Indonesia - Ahmad Ulil Albab Al Umar; Rena Soraya; Yeyen Novita; Adellia Kusuma Rachmawati; Robiatul Rifkah (Journal on Education, 2023)
This research examines the impact of the Covid-19 pandemic in Indonesia, especially in terms of economic impact and policies taken by the government and life after the Covid-19 pandemic. The research method used is qualitative. The results of this study indicate that the Covid-19 Pandemic has had a sizable impact on the economy in Indonesia. Policies and stimulus were taken so that in this new normal era, Indonesia was able to survive and rise to build the economy in Indonesia as it was before. Micro, Small and Medium Enterprises are the sector that the government prioritizes in becoming the foundation of the economy in Indonesia.